Nanog/NFATc1/Osterix signaling pathway-mediated promotion of bone formation at the tendon–bone interface after ACL reconstruction with De-BMSCs transplantation - Kai Tie (BMC, 2021)
Abstract Background Bone formation plays an important role in early tendon–bone healing after anterior cruciate ligament reconstruction (ACLR). Dedifferentiated osteogenic bone marrow mesenchymal stem cells (De-BMSCs) have enhanced osteogenic potential. This study aimed to investigate the effect of De-BMSCs transplantation on the promotion of bone formation at the tendon–bone interface after ACLR and to further explore the molecular mechanism of the enhanced osteogenic potential of De-BMSCs. Methods BMSCs from the femurs and tibias of New Zealand white rabbits were subjected to osteogenic induction and then cultured in medium without osteogenic factors; the obtained cell population was termed De-BMSCs. De-BMSCs were induced to undergo osteo-, chondro- and adipo-differentiation in vitro to examine the characteristics of primitive stem cells. An ACLR model with a semitendinosus tendon was established in rabbits, and the animals were divided into a control group, BMSCs group, and De-BMSCs group. At 12 weeks after surgery, the rabbits in each group were sacrificed to evaluate tendon–bone healing by histologic staining, micro-computed tomography (micro-CT) examination, and biomechanical testing. During osteogenic differentiation of De-BMSCs, an siRNA targeting nuclear factor of activated T-cells 1 (NFATc1) was used to verify the molecular mechanism of the enhanced osteogenic potential of De-BMSCs. Results De-BMSCs exhibited some properties similar to BMSCs, including multiple differentiation potential and cell surface markers. Bone formation at the tendon–bone interface in the De-BMSCs group was significantly increased, and biomechanical strength was significantly improved. During the osteogenic differentiation of De-BMSCs, the expression of Nanog and NFATc1 was synergistically increased, which promoted the interaction of NFATc1 and Osterix, resulting in increased expression of osteoblast marker genes such as COL1A, OCN, and OPN. Conclusions De-BMSCs transplantation could promote bone formation at the tendon–bone interface after ACLR and improve the biomechanical strength of the reconstruction. The Nanog/NFATc1/Osterix signaling pathway mediated the enhanced osteogenic differentiation efficiency of De-BMSCs.